Huang Wenda cai bi ba shi = 80 and with a many-colored brush (Xianggang Zhong wen da xue Lian he shu yuan, 2017)
Wong Man Tat had built a solid foundation in Western painting before he became a disciple of the Lingnan master Chao Shao-an. After retiring as a primary school principal, he taught painting in the Lingnan style to students throughout Hong Kong and Canada. Now in his eighties, he keeps on creating and keeps exploring in artistic technique. This collection shows some of his finest works in the last decade.